ANALISIS STRATEGI PENGEMBANGAN DESA CISONDARI MENJADI DESA WISATA DI KABUPATEN BANDUNG - Maskarto Lucky Nara Rosmadi (Master of Public Administration, Universitas Slamet Riyadi, 2018)
Rosmadi, 2018. “Analysis Of The Development Strategy Of The TouristVillage ”. Sekolah Tinggi Ilmu Ekonomi Kridatama BandungIncreasing the welfare of Cisondari Village community one of them is donethrough developing the god of tourism. The purpose of this study is toknow the concept of development of tourist villages in the VillageCisondari Bandung regency in an effort to improve prosperity bypromoting local wisdom. This research uses analytical descriptiveresearch using SWOT analysis. From the results of research conducted toobtain data that Cisondari Village has great potential, especially in thefield of tourist attraction and traditional cultural arts, so worthy to be a newtourist village in Bandung regency. Utilization of the development ofinformation technology to promote the village of Cisondari should beimproved. The role of local government and banking world is expected toencourage the development of Cisondari tourism villageKeywords: Village Tourism, Cisondari Village, SWOT Analysis